The Implementation of Social Entrepreneurship Values in Village-Owned Enterprise (BUMDes): Is it favorable? - Widiastuti, Anik; Saputri, Agatha; Riani, Lilia Pasca; Mulyani, Endang; Samsudin, Norsamsinar (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2025)
AbstractThis study focuses on the integration of social entrepreneurship values in Village-Owned Enterprises (BUMDes) in Indonesia. Aiming to assess the factors influencing the success as well as the challenges, this study emphasizes how BUMDes strategically target social problems including poverty, resource access, and economic inequality to generate positive socio-economic outcomes for the community. However, limited resources and inadequate managerial capacity are widely reported to hinder their effectiveness. This qualitative research collected the data from observation and interviews with respondents managing the BUMDes. The analysis of qualitative data from six BUMDes in Java reveals that government support, partnerships, and active community involvement are essential to address the challenges. The findings suggest that with better strategic support and community collaboration, BUMDes have the potential to achieve their social goals and support local economic resilience, making a substantial contribution to sustainable rural development in Indonesia.